Partner Selection Process in Project Alliances - Bruun, Robert (fi=Turun yliopisto|en=University of Turku|, 2018)
Prior research emphasizes the role of selecting a suitable partner for interorganizational collaboration such as alliances and partnerships. Studies show that selecting a wrong partner is one of the main reasons for strategic alliances to fail. Concurrently, cooperation is taking even more intense and closer forms. New organizational models, such as the project alliance model, emphasize the collaborative way of working in networks: the contractors, planners and the client work together to achieve the objectives of the project. In these types of projects, choosing a wrong partner would be detrimental. However, research on how companies choose their partners in project alliances is nonexistent and hence this study is first of its kind to focus on the partner selection of project alliances. The objective of the study is to examine the partner selection process in a project alliance environment. This objective is fulfilled by focusing on both the process phases in alliance formation and the factors that influence the selection of a partner. Relying on previous literature on strategic alliances, the study identifies which steps are taken in the process and which distinctive factors have an impact on the partner choice of a project alliance partner. Eight Finnish companies have been involved with the project alliance model, six of which participated in the study. The data were gathered through qualitative theme interviews among the directors of the largest infrastructure construction companies in Finland. Based on the findings of the study, a framework was established for project alliance partner selection. The framework consists of a cyclical, five-phase process. The process starts when preliminary project information about a forthcoming project reaches the potential project company. After this, the process continues with a self-assessment of the company, evaluation of potential partner, contacting and negotiations and final choice of a partner, after which the partners continue on assessing whether they need additional partners. During the process, different factors influence the partner selection. In addition to the three categories mentioned in previous literature: task-related selection factors, partner-related selection factors and learning-related selection factors, a fourth category of factors was found to affect the choice. The fourth category is named the project alliance specific selection factors. Altogether, these four categories consist of 15 specific factors. The main theoretical contribution of this thesis is shedding light to process of companies selecting partners for alliance projects. Furthermore, with the use of the framework, managers may conduct a more systematic analysis of potential partners and recognize which phases in the selection process are essential, what factors managers should affect and on the other hand, what can they improve to be more attractive as project alliance partners.